The Pricing of Interest-Rate Risk: Evidence from the Stock Market - Sweeney, Richard J.; Warga, Arthur D. (Journal of Finance, 1986)
This paper addresses the issue of whether firms are required to pay an ex ante premium to investors for bearing the risk of interest-rate changes. A two-factor APT model with the market and changes in the yield on long-term government bonds as factors is employed. The paper shows that, empirically, most of the interest-sensitive stocks are in the utility industries, and that there is reasonable evidence that the interest factor is priced in the sense of the APT. Several sources for the interest sensitivity are considered, and regulatory lags are focused on as a likely candidate.